The simplification of 3log(x + 4) – 2log(x – 7) + 5log(x - 2) - log(x^2) is
<u>Solution:</u>
Given, expression is
We have to write in as single logarithm by simplifying it.
Now, take the given expression.
Rearranging the terms we get,
Hence, the simplified form
Answer:
3x-4y=-16
Step-by-step explanation:
Answer:
G
Step-by-step explanation:
Try to understand what this equation is saying and what plugging in different values would represent.
At x=0, b(0)=850; which means the initial balance is $850. So H is incorrect.
At x=1, b(1)=871.25; which means that after 1 year, the initial balance will have increase to $871.25. So J is incorrect.
Since the initial vacation of 850 is being multiplied by a factor which is greater than one, the balance will be increased each year. So F is incorrect.
Finally, if we look at the factor by which we are multiplying, do a simple Algebraic step, and convert it into percentages we get:
1.025 = (1 + 0.025) = 100% + 2.5%
Essentially this is showing us that the balance will increase by 2.5% on however much is in the account each year.
So G is your answer.
Step-by-step explanation:
Hey there!
Given;
[A = 1/2b*h]
Divide both sides by 'h'.
A/h = 1/2(b*h/h) [ on right side'h' gets cancelled].
Multiply '2' and 'A'.
A*2/h = b
b = 2A/h.
<em><u>Hope</u></em><em><u> </u></em><em><u>it helps</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em>